Co-construction of an assessment method of the environmental sustainability for cattle farms involved in a Protected Designation of Origin (PDO) cheese value chain, Cantal PDO. (May 2017) - Laurent, Claire; Hulin, Sophie; Agabriel, Claire; Chassaing, Chantal; Botreau, Raphaëlle; Monteils, Valérie
Highlights: An assessment method of the environmental sustainability for dairy farms. A multi-criteria assessment procedure based on a hierarchical structure. An assessment method fully built with the stakeholders. A transparent and operational assessment method. Numerous indicators created for the management of grassland resources. Abstract: In France, numerous Protected Designation of Origin (PDO) cheese value chains have revised their specifications to address environmental protection, particularly at the farm level. In this stage, it is nevertheless impossible to state whether the proposed modifications may ensure the sustainability of environmental protection as no environmental sustainability diagnostic has been conducted. The aim of this study is to construct an assessment method for the Cantal PDO farms. A multi-criteria assessment approach was implemented in the following 5 steps: definition of the framework of the study, determination of the principles and criteria, definition of the indicators, aggregation of all elements of the assessment, and finally, test of the assessment method on farms. Focus groups meetings were organised for the first four steps. The panel discussions were based on data obtained from both the literature and surveys of stakeholders operating in the value chain and within the territory. The obtained assessment method comprises 4 principles characterised by 33 indicators. The most important principle (45%), management of grassland resources, is a key economic and environmental point of the studied farms. It reflects the necessary intensive use of grass by the animals in the PDO farms. Few existing methods addressed this principle that required the design of several new indicators. The second principle, impact of agricultural practices (25%), is often included in environmental sustainability assessment methods The adopted indicators are, thus, drawn from existing methods and adapted to the context of the farms studied. The management of the farm buildings and the landscape principle (18%) is often considered in social sustainability. Its role in environmental sustainability can be explained by its strong link with the image of PDO products. Primarily drawn from the literature, the used indicators have been extended to make the assessment method as objective as possible. Finally, the management of local, energy and water resources principle has the lowest weighting (12%). This can be explained by the limited number of indicators. This assessment method was constructed for the Cantal PDO farms by considering their environment and particularities. In consequence, the stakeholders have taken ownership of it. It could be used by other ruminant systems based on grassland. The development of numerous indicators enhanced the pool of existing indicators. This assessment method was sensitive and allowed for the discrimination between farms.